One-step phase transferring method on preparing CuInS2/ZnS QDs dispersion via ultrasonic treatment for bioimaging - Permadi, Adi; Shitophyta, Lukhi Mulia; Satar, Ibdal (International Journal of Advances in Applied Sciences, 2024)
Sonochemistry has many applications in biomedical engineering owing to its ability to break chemical bonds. It can also be used to facilitate the preparation of aqueous quantum dots (QDs) dispersions during microemulsion formati on. Cavitation, bubble growth and collapse during sonication facilitate the formation of microemulsions between a solvent and water. Sonication was employed in this study to prepare aqueous copper indium sulfide colloidal zinc sulfide (CuInS2/ZnS) QD dispersions using different solvent systems. The resultant QDs were characterized by UV-vis absorption, photoluminescence, and dynamic light scattering. Hexane was determined to be the best solvent for the preparation of QD dispersions with the resultant QDs (30 nm in diameter) retaining their chemical integrity and >30% of their quantum yield. CuInS2/ZnS QD dispersions in water can be directly prepared without any non-polar solvent and it has shown high quantum yield. Further, it was also shown that less-toxic, which is efficient in labeling tumor cells derived from human liver cancer (HepG2). It’s evident that, sonication was found to be an efficient alternative approach for preparing aqueous QD dispersions without the need for surface modification, or the use of non-polar solvents during microemulsion formation.